Sleeping on the wing an anthology of modern poetry with essays on reading and writing - Koch, Kenneth 1925-2002 (Vintage Books, 1982)
Selections from the work of twenty-three modern poets, from Emily Dickinson and Gerard Manley Hopkins to Gary Snyder and Leroi Jones, including translations of poems by five European poets.